2018
DOI: 10.1002/dneu.22622
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid flow increases from newborn to adult stages

Abstract: Solute transport through the brain is of major importance for the clearance of toxic molecules and metabolites, and it plays key roles in the pathophysiology of the central nervous system. This solute transport notably depends on the cerebrospinal fluid (CSF) flow, which circulates in the subarachnoid spaces, the ventricles and the perivascular spaces. We hypothesized that the CSF flow may be different in the perinatal period compared to the adult period. Using in vivo magnetic resonance imaging (MRI) and near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Fluid transport in perivascular pathways has been implicated in clearance of solutes and proteins from the brain ( Iliff et al, 2012 ; Lundgaard et al, 2017 ; Mestre et al, 2018 ; Xie et al, 2013 ) but has been sparsely studied in development ( Di Palma et al, 2018 ). A recent MRI study demonstrated that the glymphatic system is developed by P90, although statistical significance was not indicated between P28 and P90 ( Di Palma et al, 2018 ). Because of the resolution limitations of MRI, our study adds a characterization of perivascular CSF influx in early postnatal ages.…”
Section: Discussionmentioning
confidence: 99%
“…Fluid transport in perivascular pathways has been implicated in clearance of solutes and proteins from the brain ( Iliff et al, 2012 ; Lundgaard et al, 2017 ; Mestre et al, 2018 ; Xie et al, 2013 ) but has been sparsely studied in development ( Di Palma et al, 2018 ). A recent MRI study demonstrated that the glymphatic system is developed by P90, although statistical significance was not indicated between P28 and P90 ( Di Palma et al, 2018 ). Because of the resolution limitations of MRI, our study adds a characterization of perivascular CSF influx in early postnatal ages.…”
Section: Discussionmentioning
confidence: 99%
“…Early life is a critical period of brain development. Recent studies have shown that the glymphatic system in the rodent brain develops early in life 14,15 . For instance, Munk et al.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the glymphatic system in the rodent brain develops early in life. 14,15 For instance, Munk et al found that glymphatic flow in the mouse brain gradually increased with age. They further found that glymphatic flow displayed initial signs in the circle of Willis at embryonic period 17.5, started in the HPC at P1, and ultimately matured at P14.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have investigated the age dependency of CSF flow values, 14,31,[42][43][44][45] demonstrating age dependence of CSF flow parameter, 14,45 with significantly reduced CSF stroke volumes in the elderly. 31 However, Lokossou et al 44 suggested that aging mainly changes cerebral blood flow but preserves blood and CSF interactions, with an age-independent positive correlation between blood and CSF stroke volumes.…”
Section: Discussionmentioning
confidence: 99%